Answer:
[tex]g^{-1}(x) = \sqrt[3]{\frac{x - 5}{4}}[/tex]
Step-by-step explanation:
To find the inverse of a function, you can switch the "x" and "y" variables, then isolate "y", then change it back to function notation with the superscript ⁻¹.
You can't see "y" in the given function, but y = g(x). g(x) is the way you write "y" in function notation. The inverse function notation is g⁻¹(x).
[tex]g(x) = 4x^{3} + 5[/tex]
[tex]y = 4x^{3} + 5[/tex] Change "g(x)" to "y"
[tex]x = 4y^{3} + 5[/tex] Switch the "x" and "y" variables
[tex]x - 5 = 4y^{3} + 5 - 5[/tex] Subtract 5 from both sides to start isolating "y"
[tex]x - 5 = 4y^{3}[/tex] 5 - 5 cancels out on right side
[tex]\frac{x - 5}{4} = 4y^{3}/4[/tex] Divide both sides by 4
[tex]\frac{x - 5}{4} = y^{3}[/tex] 4y³/4 cancels out the 4 on the right side
[tex]\sqrt[3]{\frac{x - 5}{4}}= \sqrt[3]{y^{3}}[/tex] Cube root both sides
[tex]\sqrt[3]{\frac{x - 5}{4}} = y[/tex] ∛y³ cancels out the ³ on the right side
[tex]y = \sqrt[3]{\frac{x - 5}{4}}[/tex] Variable on left side is standard formatting
[tex]g^{-1}(x) = \sqrt[3]{\frac{x - 5}{4}}[/tex] Change the inverse function notation g⁻¹(x)
The inverse of g(x) = 4x³ + 5 is g⁻¹(x) = ∛[(x-5)/4].